Penggunaan Rasio Keuangan untuk Menilai Kinerja Keuangan pada PT Mitra Keluarga Karya Sehat Periode Tahun 2018-2021 - Ghina Kemala Dewi; Ayu Kartika (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study aims to analyze the financial performance of PT Mitra Keluarga Karyasehat Tbk before and during the COVID-19 pandemic, where healthcare facilities were among the most crucial and highly needed aspects for recovery from the contagious COVID-19 outbreak. The method used in this research is a quantitative approach. The type of data utilized is secondary data obtained from the Indonesia Stock Exchange or the official website of PT Mitra Keluarga Karyasehat Tbk. The data consists of financial reports from the 2018-2019 period, representing conditions before the COVID-19 pandemic, and the 2020-2021 period, representing conditions during the pandemic. The research variables include liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The results of this study indicate that during the pandemic, the financial performance of PT Mitra Keluarga Karyasehat Tbk experienced fluctuations. Before the pandemic, financial performance showed an upward trend, but it declined in the early year of the pandemic, 2020. However, in 2021, financial performance increased again.